Performance of Chrysanthemum or Chrysanthemum Morifolium Ramat (CV. Balady) in Different Saline Water Irrigated Soils and Growing Media - Amarin, R.; Kafawin, O.; Ayad, J.; Al-Zyoud, F.; Haddad, N.; Amarin, A. (Jordan Journal of Agricultural Sciences, 2021)
As a result of the decreasing availability of high-quality irrigation water, the salinity tolerance of cut flowers is of increasing importance. The influence of salinity on the growth and quality of Chrysanthemum, Chrysanthemum morifolium L. grown in two different media under four salinity levels was evaluated. C. morifolium plants were grown in plastic pots containing either zeolitic tuff or soil as potting media. Seedlings of C. morifolium were subjected to four NaCl/CaCl2 salinity levels (2, 4, 6, and 8 dS.m-1). The effect of increasing salinity level on growth, flowering characteristics, time to flower, length and diameter of flowering shoots, and the diameter of the terminal flower on each stem were evaluated. On termination of the experiment, plant height, two perpendicular canopy widths, and fresh and dry weights of shoots were measured. Results indicated that most of all measured characteristics were reduced in response to increasing salinity levels. Increasing salinity levels caused significant reductions in plant height, fresh and dry yield, and relative water content. Moreover, salinity reduced flower quality (color, size, stem thickness, and length) and yield. Also, some physiological changes occur in stomatal conductance, leaf relative water content, and chlorophyll content. C. morifolium plants showed a good salinity resistance by irrigating plants with saline water up to 4 dS.m-1. Significant differences in C. morifolium plant responses were also detected between soil and zeolitic tuff media for most tested characteristics, in which using zeolitic tuff as rowing media was better to cope with higher salinity levels than plants grown in soil. In conclusion, it is recommended to use zeolitic tuff instead of soil when water salinity is a problem in irrigation water.